Application of morphometric measures in estimation of body weight and discrimination of Astyanax lacustris and Astyanax fasciatus - Botelho, Hortência Aparecida; de Assis Lago, Aline; da Costa, Alisson Lucrecio; Costa, Adriano Carvalho; Reis Neto, Rafael Vilhena [UNESP]; Silva, Zoraia; Ribeiro, Fagner Machado; Café, Marcos Barcellos; de Freitas, Rilke Tadeu Fonseca (Hindawi, 2019)
The objective of this study was to verify the direct and indirect correlation between morphometric measures, ratios, body weight and yield in two lambari species Astyanax lacustris and Astyanax fasciatus and whether the discriminant analysis is capable of separating and allocating the species. We used 102 lambari yellow tail and 60 lambari red tail. The fish were weighed and submitted to the evaluation of the morphometric measurements. The direct and indirect effects were evaluated by the method of track analysis, considering weight at slaughter, weight of body parts and body yields as dependent variables and measures and morphometric ratios as explanatory variables. Astyanax lacustris presented higher height and body width, carcass yield and trunk, while A. fasciatus presented higher head yield and viscera weight. The discriminant analysis was able to classify 79.5% of the two species. Track analysis demonstrated that the morphometric measurements can be used for estimation of body and body components’ weight in A. lacustris and A. fasciatus. However, regarding the corporal yield; the morphometric measures were insufficient to explain the yield variations of the species.
Keywords: carcass; direct and indirect effect; lambari; yield